PSYCHOLOGICAL DISTRESS AND QUALITY OF LIFE AMONG PEOPLE WITH CONGENITAL AND ACQUIRED PHYSICALLY DISABILITIES - Ayub, Sara; Erum Irshad, Erum Irshad; Hameed, Nadia (Pakistan Journal of Clinical Psychology, 2025)
Objectives: The aim of the current study was to investigate the difference in the levels of psychological distress and quality of life among people with congenital and acquired physical disabilities. Design of the Study: Cross-sectional research design. Place and Duration of Study: Data was collected from September 2023 to January 2024, at the University of Peshawar. Sample and Method: The sample consisted of individuals with physical disabilities (N=80) with the age range between 18-65 years (X=35.11, SD= 14.49) were selected through purposive sampling technique from the OPDs of various health care setups dealing with physical disabilities. DASS-21 and WHO Quality of Life Scale were used as study tools. Results and Conclusion: The finding indicated that people with congenital physical impairment experienced lower levels of stress and depression as well as higher quality of life than those who acquired them; however, no significant difference was found in the score of anxiety of both groups. The findings reveals the psychological challenges encountered by people having physical limitations, and the need for specialized mental-health treatments and rehabilitation, as well as role of social support to improve coping mechanisms and overall quality of life.